Análisis del mercado y las potencialidades de desarrollo de los restaurantes de comida rápida en la ciudad de Riobamba período 2010- 2014 - Galeas Martínez, Darwin Jhonny (2025)
The study of market analysis and its development potential significantly influences fast - food restaurants in the city of Riobamba during the period 2010-2014. By innovating and creating new restaurants with better quality and a variety of products, businesses can compete effectively and achieve a strong reception from customers. This research focuses on market analysis to understand how fast-food restaurants develop in a large and saturated market. By examining these factors, we can determine the strategies and techniques used by each restaurant to achieve strong market positionin g against competitors. After conducting the market study, we identified people’s preferences for fast food, including quality, price, and hygiene when purchasing certain types of meals. The high demand from potential customers and their frequent consumption patterns contribute to the continued growth of these establishments.